DIVERSIFIKASI PRODUK MURABAHAH DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF PADA KSPPS GUMARANG AKBAR SYARIAH MATARAM - Yanti, Fenti Fifi; Mahmud, Agus; Susianti, Nurul (Islamic Banking and Finance, 2023)
This study aims to see the diversification carried out by KSPSS Gumarang Akbar Syariah Mataram in increasing customers or prospective members and increasing competitive advantage. Diversification in the form of product diversification aimed at meeting market needs and maintaining excellence in the midst of intense competition. Based on the results of the study, it shows that the diversification of Murabahah Products is in the form of Murabahah Bil Wakalah Products. The difference in terms of the margin obtained from Murabahah Bil Wakalah products is 1.3%, while for Murabahah financing it is 1.5%. Judging from the data on the significant increase in the number of customers from the use of Murabahah contracts as many as 84, 102 and 120 customers in 2019-2021, accompanied by innovations carried out, the number of customers using innovative products was 112,117,143 customers/members in 2019-2021. This is a promising opportunity to increase the advantages of KSPPS Gumarang Akbar Syariah Mataram.